Collaborative research for justice and multi-issue movement building: Challenging discriminatory policing, school closures, and youth unemployment - Glass, Ronald David; Stoudt, Brett G. (Education Policy Analysis Archives, 2019)
This special issue engages ethical, epistemic, political, and institutional issues in projects of collaborative research for justice that were designed with movements contesting policing, school closures, and youth disinvestment and unemployment. Three of the articles were collaboratively written by activists and scholars who drew from movements that deployed research for community-driven progressive change. The movements and the research are thus situated at the intersection of struggles against a resurgent anti-immigrant white supremacy, gentrification, a punitive carceral state, low pay and lack of meaningful employment opportunities, and the privatization of the public sector. These articles build upon and are in conversation with a set of related articles published in the spring 2018 special issue of Urban Education(Warren et al, 2018) that also addressed ethical, epistemic, political, and institutional tensions in collaborative research for justice. This EPAA special issue aims to advance the discussion through deep reflection within the context of focal ‘cases’ and within efforts to open space within universities for modes of engaged scholarship that can respond to the challenges of the current moment, as described in the articles that bookend the cases. Taken all together, this special issue demonstrates how scholars, educators, teachers, activists, community leaders, and policy makers can use the production and mobilization of knowledge as a force for building, supporting, sustaining, and advancing multi-issue movements for justice not just in schools and the academy but also in communities of color and others aggrieved by current inequities.